Cytological Localization of Dengue-2 Antigens: an Immunological Study with Ultrastructural Correlation - Cardiff, R. D. (1973)
Immunofluorescence and electron microscopy were used to study the development and cytological distribution of dengue-2 virion and nonvirion antigens in monkey kidney cells. The type and combination of fixatives were found to affect the intensity of fluorescence. Paraformaldehyde fixation alone resulted in a low level of fluorescence, but an additional fixation step with ethanol or acetone resulted in maximum staining. No fluorescence was obtained after fixation with glutaraldehyde alone or in combination with other solvents. Methanol caused selective ablation of fluorescence by antibody to purified virions. Dengue-specific fluorescence that was most intense in the perinuclear area radiated in a granular pattern of decreasing intensity into the cytoplasm. The perinuclear fluorescence was associated with nonvirion antigens and the cytoplasmic fluorescence was associated with virion antigens. Electron micrographs of infected cells revealed vesicular bodies with reticular electron-dense centers, clusters of structurally complete virions deep within the endoplasmic reticulum, and single virus particles in vacuoles near the periphery of the cell.